Polyacroasis as a componet of rhetorical comunication. - Albaladejo, Tomás (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
In this paper I deal with lhe characteristics of the hearer of rhetorical discourse and the differences existing between the hearers of different discourses and between the hearers of the same discourse. I propose the notion and the term of polycroasis in order to explain the different functions, attitudes and interpretations of a discourse that is archived by is hearers, who are characterized by multiplicity and diversity. Special attention is paid to the polyacroasis based on the difference between the hearers who may make decisions as to discourses and those others who not decide. Starting out from rhetoric, polyacroasis is taken into account as a component of general communication and, hence, also of a communication of oral literature.